Combined Chair-Based Exercises Improve Functional Fitness, Mental Well-Being, Salivary Steroid Balance, and Anti-microbial Activity in Pre-frail Older Women - Furtado, Guilherme Eustáquio; Letieri, Rubens Vinícius; Silva-Caldo, Adriana; Trombeta, Joice C. S.; Monteiro, Clara; Rodrigues, Rafael Nogueira; Vieira-Pedrosa, Ana; Barros, Marcelo Paes; Cavaglieri, Cláudia Regina; Hogervorst, Eef; Teixeira, Ana Maria; Ferreira, José Pedro (Frontiers in Psychology, 2021)
Introduction: Regular exercise has long been shown to positively impact the immune system responsiveness and improve mental well-being (MWB). However, the putative links between biomarkers of mental health and immune efficiency in exercising subjects have been scarcely investigated. The aim of this study was to verify the effect of a 14-week combined chair-based exercise program (CEP) on salivary steroid hormones and anti-microbial proteins, functional fitness and MWB indexes in pre-frail older women. Methods: The participant women (82.8 ± 4.6 years-old; n=32) were randomly divided into the exercising group (CEP, n=17) and the non-exercising control group (CG, n=15). The pre/post assessment included: i) salivary anti-microbial proteins lysozyme (Lys) and immunoglobulin-A (IgA); ii) salivary steroid hormones of testosterone (TT) and cortisol (COR); iii) functional fitness (gait speed, hand grip strength and static balance); iv) MWB questionnaires (happiness, depression state, satisfaction with life and stress). Results: Significant differences with large Cohen’ (d) effect sizes were found on increased salivary TT (p < 0.05; d = 0.60) after exercise intervention. The results revealed a decrease in IgA levels after CEP (p < 0.01, d = 0.30). The increased in subjective happiness levels (p < 0.05, d = 0.30) and decrease of stress perception (p < 0.01, d = 2.60) and depressive state (p < 0.05, d = 0.30) were found after intervention in the CEP group. Robust statistical differences in gait speed (p <0.05; d = 0.60) and balance tests (p < 0.05; d = 0.80) were also found in the CEP group. In control, COR increased moderately (p < 0.05; d = 0.65) while no changes were found for the other indicators. Correlation analyses showed inter-dependence between pre-post variations of MWB, biochemical indexes and fitness function (e.g. COR inverse correlation with hand grip strength and balance tests). Conclusion: The CEP program was able to improve functional-fitness performance, decrease feelings of stress and increase happiness. The CEP also induced clinically relevant hormonal and immune responses, which suggests that chair-exercises that combines muscular-strength, balance and gait speed training are promising interventions to improve physical and mental health of older pre-frail adults.